Glyceraldehyde 3-phosphate dehydrogenase-telomere association correlates with redox status in trypanosoma cruzi - Pariona-Llanos, Ricardo; Pavani, Raphael Souza; Reis, Marcelo; Noel, Vincent; Silber, Ariel Mariano; Armelin, Hugo Aguirre; Cano, Maria Isabel Nogueira [UNESP]; Elias, Maria Carolina (Public Library Science, 2015)
Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) is a classical metabolic enzyme involved in energy production and plays a role in additional nuclear functions, including transcriptional control, recognition of misincorporated nucleotides in DNA and maintenance of telomere structure. Here, we show that the recombinant protein T. cruzi GAPDH (rTcGAPDH) binds single-stranded telomeric DNA. We demonstrate that the binding of GAPDH to telomeric DNA correlates with the balance between oxidized and reduced forms of nicotinamide adenine dinucleotides (NAD+/NADH). We observed that GAPDH-telomere association and NAD+/NADH balance changed throughout the T. cruzi life cycle. For example, in replicative epimastigote forms of T. cruzi, which show similar intracellular concentrations of NAD+ and NADH, GAPDH binds to telomeric DNA in vivo and this binding activity is inhibited by exogenous NAD+. In contrast, in the T. cruzi non-proliferative trypomastigote forms, which show higher NAD+ concentration, GAPDH was absent from telomeres. In addition, NAD+ abolishes physical interaction between recombinant GAPDH and synthetic telomere oligonucleotide in a cell free system, mimicking exogenous NAD+ that reduces GAPDH-telomere interaction in vivo. We propose that the balance in the NAD+/NADH ratio during T. cruzi life cycle homeostatically regulates GAPDH telomere association, suggesting that in trypanosomes redox status locally modulates GAPDH association with telomeric DNA.